Effectiveness of Audiovisual Animation Education as an Effort to Increase Knowledge To Prevent the Risk of Falling Patients in Hospital - Aprin Rusmawati; Putri Kristyaningsih; Alfian Fawzi (PT. Griya Eka Sejahtera, 2023)
Background: The risk of falling is one aspect that needs to be studied in patient safety, especially for patients who have a risk of falling due to weakness or the effects of therapy. It can cause injury, increasing the patient’s long of stay, and patient’s treatment fees. The other effects of this are physical injury including scratch, torn, bruised even it can cause fracture, bleeding and head injury. The purpose of this study was to determine the effectiveness of providing audiovisual animation education as an increase in knowledge of efforts to prevent falls in patients in hospitals.Methods: This study uses a quasi-experimental research design with a one group pretest posttest approach without a control group. The research was conducted at Gambiran Hospital. The sampling technique used a purposive sample technique, namely by determining certain criteria. Data were collected using a questionnaire sheet, bivariate analysis using the Paired Sample T-Test with the help of SPSS.Results: Based on the results of statistical tests, it is known that the value of sig. (2-tailed) of 0.000 <0.05, meaning that H1 is accepted, it can be concluded that audiovisual animation education is effective as an effort to prevent the risk of falling in patients in the hospital.Conclusion: Animated audiovisual education is very effective to increase respondent’s knowledge in preventing patient fall. With the guaranteed patient safety it will affect patient’s recovery. The guaranteed patient safety can not be separated from the hospital monitoring and family caring to avoid from various risks than can be occured, one of this risk is risk of patient fall. This audiovisual methods is a good method to increase knowledge, because this method involve more sense in learning process, both sense of sight and sense of hearing.